2008
DOI: 10.1002/glia.20628
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 15 expression in the CNS: Blockade of its activity prevents glial activation after an inflammatory injury

Abstract: Although reactive glia formation after neuronal degeneration or traumatic damage is one of the hallmarks of central nervous system (CNS) injury, we have little information on the signals that direct activation of resting glia. IL-15, a pro-inflammatory cytokine involved in regulating the response of T and B cells, may be also key for the regulation of early inflammatory events in the nervous system. IL-15 was expressed in the CNS, most abundantly in cerebellum and hippocampus, mainly in astrocytes and in some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
57
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 53 publications
8
57
0
2
Order By: Relevance
“…Moreover, several studies have documented the capacity of human monocytes/ macrophages for providing functional IL-15 to T cells (20,23), supporting the notion that CNS macrophages and most likely microglia do the same. In line with our findings, astrocytes have been shown to be the main source of IL-15 in LPS-injected mice, with reactive microglia being an additional source (38). Dendritic cells, found mainly in the perivascular spaces in MS lesions, could serve as an additional source of IL-15 (21).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Moreover, several studies have documented the capacity of human monocytes/ macrophages for providing functional IL-15 to T cells (20,23), supporting the notion that CNS macrophages and most likely microglia do the same. In line with our findings, astrocytes have been shown to be the main source of IL-15 in LPS-injected mice, with reactive microglia being an additional source (38). Dendritic cells, found mainly in the perivascular spaces in MS lesions, could serve as an additional source of IL-15 (21).…”
Section: Discussionsupporting
confidence: 88%
“…Thus, it is essential to document functional surface IL-15 protein expression in human CNS cells. Although the IL-15 protein has been detected on astrocytes in inflammatory mouse models (36,38), whether these nonmyeloid cells represent an important and functional IL-15 source in human CNS diseases specifically for CD8 T cells has not been addressed. Astrocytes are implicated as contributors to both innate and adaptive immune responses taking place in the CNS (39).…”
Section: Ultiple Sclerosis (Ms)mentioning
confidence: 99%
“…Mice perfusion, tissue processing and immunohistochemical analysis was performed as previously described (Gomez-Nicola et al , 2008, 2014) using the following primary antibodies: rabbit anti-PCNA (Abcam), rabbit anti-phospho-Histone H3 (Cell Signaling), rabbit anti-Ki67 (Abcam), mouse anti-BrdU (DSHB), rat anti-BrdU (Santa Cruz Biotechnologies), goat anti-doublecortin (DCX; Santa Cruz Biotechnologies), guinea pig anti-doublecortin (DCX; Millipore), rabbit anti-calretinin (Millipore), goat anti-Sox2 (Santa Cruz Biotechnologies), mouse anti-NeuN (Millipore), mouse anti-synaptophysin (Millipore) and rabbit anti-cleaved caspase 3 (Millipore). After primary antibody incubation, the sections were washed and incubated with the appropriate biotinylated secondary antibody (Vector Labs), and/or with the appropriate Alexa Fluor® 405, 488 or 568 conjugated secondary antibody or streptavidin (Molecular Probes).…”
Section: Methodsmentioning
confidence: 99%
“…Some studies have demonstrated that IL-15 contributes to the immunopathology of several inflammatory diseases, such as rheumatoid arthritis and inflammatory bowel disease (26,27). Despite recent studies suggesting astrocytes as a major source of IL-15 in the inflamed CNS (28)(29)(30), the potential role of astrocytic IL-15 in ischemic brain injury remains elusive.…”
mentioning
confidence: 99%